2020
DOI: 10.1007/s10461-020-02802-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Suicidal Ideation on Child Cognitive Development: A Longitudinal Analysis

Abstract: This study aimed to assess the association between suicidal ideation among mothers living with HIV in Zimbabwe and the cognitive development of their children. Participants were mother-child dyads recruited from two rural districts in Zimbabwe. Data were collected at baseline and 12 months follow-up. Suicidal ideation was assessed using item-10 from the Edinburgh postnatal depression scale. Mixed-effects linear regression was used to assess the association of child cognitive outcomes at follow-up (using the Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Having a major depressive episode, an anxiety disorder or a previous suicide attempt throughout life are also risk factors (Onah et al, 2017 ). Mebrahtu et al ( 2020 ) also identified high stress and symptoms of depression as risk factors. Pregnant women with insomnia and high rumination have higher rates of suicidal ideation than the general population (Kalmbach et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Having a major depressive episode, an anxiety disorder or a previous suicide attempt throughout life are also risk factors (Onah et al, 2017 ). Mebrahtu et al ( 2020 ) also identified high stress and symptoms of depression as risk factors. Pregnant women with insomnia and high rumination have higher rates of suicidal ideation than the general population (Kalmbach et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Musyimi et al ( 2020 ) also identified low economic status and intimate partner violence as consistently associated factors. Women who reported suicidal ideation tend to be young, single and experienced hunger (Mebrahtu et al, 2020 ). The religious belief that premarital sex is wrong is also related to a high risk of suicidal ideation (Chan et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suicide prevention and risk reduction should be key intervention targets since maternal death by suicide has a profound effect on the woman’s child(ren), including loss of a primary care giver, feelings of separation and abandonment ( 8 ), increased rate of depressive symptoms ( 9 ), increased risk of bipolar disorder ( 10 ), and an increased risk of death by suicide themselves ( 11 ). Furthermore, maternal suicidal ideation alone has been associated with poorer child cognitive outcomes, including motor skills and language development ( 12 ).…”
Section: Introductionmentioning
confidence: 99%